Pengaruh Iklan Online dan Citra Merek Terhadap Minat Beli Dengan Kepercayaan Merek Sebagai Variabel Intervening pada Toko Online Shopee di Makassar - Nugroho, Muhammad Iqbal Yudha; Efendi, Ahmad; Abdullah, Wahidah - (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
ABSTRACT This study aims to determine the effect of online advertising and brand image on buying interest with brand trust as an intervention variable at the online shopee shop in Makassar. This study uses primary data by taking data from the distribution of questionnaires. The sampling technique in this study is purposive sampling so that the number of samples used is 130 people. The data analysis technique in this study uses path analysis using SPSS which is directed to examine the relationship between online advertising and brand image variables on buying interest with brand trust as an intervention variable at the online shopee shop in Makassar. The results of this study indicate that online advertising has a positive and significant effect on brand trust. Brand image has a positive and significant effect on brand trust. Brand trust has a positive and significant effect on buying interest. online advertising has a positive and significant effect on buying interest. Brand image has a positive and significant effect on buying interest. Online advertising through brand trust has a positive and significant effect on buying interest. Brand image through brand trust has a positive and significant effect on buying interest. Keywords: Online advertising, Brand image, Brand trust, and Buying interest